The effect of service quality on consumer satisfaction of Aqualis Fabricare Laundry & Green Dry Clean in Bandar Lampung - Gitayani, Aurelia Udella; Ahmad, Aripin (Asian Journal of Economics and Business Management, 2025)
A company's business must adhere to concepts that ultimately lead to customer satisfaction. This is especially true for service businesses, which differ significantly from physical goods businesses. Aqualis Fabricare Laundry & Green Dry Clean in Bandar Lampung is required to provide excellent service to ensure customer satisfaction. Therefore, this study examines whether the five dimensions of service quality indicators—Physical Evidence, Reliability, Responsiveness, Assurance, and Empathy—have the same impact on customer satisfaction at Aqualis Fabricare Laundry & Green Dry Clean in Bandar Lampung. The hypothesis of this study is that all five dimensions of service quality indicators have a positive and significant impact on customer satisfaction at Laundry & Green Dry Clean. Data collection was done through questionnaires with a sample of 100 customers. The results from multiple regression analysis show a significant impact. The F-test result indicates that the independent variables, taken together, significantly affect customer satisfaction at Laundry & Green Dry Clean, with a calculated significance value of 0.000, which is smaller than the alpha value of 5%. The partial test using the t-test also shows that each independent variable influences the dependent variable, customer satisfaction at Laundry & Green Dry Clean in Bandar Lampung. Thus, the hypothesis formulated is supported.